Persepsi Generasi Z dengan Pernyataan “Kerja Sesuai Passion” dalam Menentukan Profesi - Octavia, Shinta; Sari, Wulan Purnama (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
This research was conducted because researchers wanted to see Generation Z's (Gen Z) perceptions of the statement